(untitled) (Experimental biology, 2015)
Searching of new strains of antagonist bacteria of phytopathogenic fungi, adapted to the specific soil and climatic conditions, is still remaining as one of the actual researches at the moment. 112 strains of Bacillus thuringiensis bacteria were extracted from 22 soil samples of southern Kazakhstan, which can inhibit the growth of phytopathogenic fungus Fusarium solani, the causative agent of stem disease of Ulmuspumila L. The highly effective strain 4ant was isolated and identified by molecular-genetic method among them, which apart from F.solani also inhibits the growth of many pathogenic fungi such as F. oxysporum, Mucorcircinelloides f. circinelloides, Rhizoctonia solani. A wide range of antagonistic properties of Bacillus thuringiensis 4ant strain justifies its practical value as useful agent in biological control of diseases of South Kazakhstan’s dendroflora.